Neuropsychological Profile in Hutchinson-Gilford Syndrome: Analysis of a Rare Case - Souza, Marina Maria Barbieri de; Figueiredo , Mônica Briglia (Brazilian Journal of Case Reports, 2025)
Hutchinson-Gilford Syndrome, also known as Progeria Syndrome, is a rare genetic disorder that leads to premature aging and accelerates the cellular aging process, affecting the cognitive, motor, and social functions of affected children. This study presents the neuropsychological assessment of two 3-year-old patients diagnosed with the syndrome, aiming to map their cognitive, emotional, and behavioral profiles. The evaluation included interviews with family members, clinical observation, and the application of tests such as the Bayley-III Scale and the Son-R Test. The results indicated significant delays in cognitive, motor, and communicative abilities in both patients, with developmental ages below their respective chronological ages. Based on these findings, a multidisciplinary approach involving speech therapy, occupational therapy, and physical therapy is recommended to stimulate the affected areas and develop family support strategies to promote better social and functional adaptation.